A Brief Data on Water Demand Assessment for Sustainable Potable Water Supply in Yergalem Tula Kebele, Ethiopia. (18th August 2022) - Vijayan, D. S.; Tadesse, Henok Tsegaye; Yokamo, Yohanan; Divahar, R.; Bezabih Bashe, Thomas; Jebasingh Daniel, J.
Abstract : In spite of Ethiopia's abundant water resources, such as rainwater, groundwater, river, and lake, there has been an increase in the demand for potable water during the past decade. Since 1990, Ethiopia has only achieved 57 percent of the Millennium Development Goal target for access to safe drinking water. Inadequate access to clean potable water and sewerage services and lack of good hygiene practices have a negative impact on health and nutrition, such as diarrheal disease which is one of the leading causes of mortality among children under the age of five in Ethiopia. The objective of the present study is to assess the water demand in Yergalem Tula Kebele, which will be used in the sustainable potable water supply design for the city. The water demand analysis is based on a geometric method of population forecasting with an annual growth rate of 3%. The total water demand (domestic and nondomestic water demands) projection has also been made and the per capita water demand of 25 liters for a distance of 0.5 km from the water distribution point for rural piped water supply system is adopted, as per GTP-II minimum service level. The mode and level of services considered for community water supplies include public fountains and institutions (i.e., schools and health centers/posts) with stand water points.